Cladonia confusa fm. confusa f. confusa - Yánez-Ayabaca, A.; Ahti, T.; Bungartz, F. (Zenodo, 2013)
Cladonia confusa f. confusa (Figs. 3a, c–d) Podetia yellowish to green gray, with pale brown tips. Spot tests and chemistry : P−, K−, C−, KC+ yellow, UV+ bright greenish white; perlatolic and usnic acids (perlatolic acid rarely absent and then UV–, see notes below). Distribution and ecology : Known from Fernandina, Isabela, Pinta, Pinzón, San Cristóbal, Santa Cruz, and Santiago Island. The most common Galapagos reindeer lichen. Often the dominant taxon in lichen heaths of the humid highlands, where it can form gigantic cusions up to several meters in diameter. Few specimens have also been collected in humid habitats at lower altitudes, in the transition or even dry zone. Notes : The large mayority of specimens of C. confusa f. confusa contains perlatolic acid and thus fluoresces a bright greenish white under UV light. This is not the case, however, for some specimens that also morphologically differ from typical C. confusa f. confusa . These specimens that lack perlatolic acid contain an unidentified substance that forms a pale spot at R f 1−2 in solvent A. Morphologically the latter two chemotypes are very similar and extremely difficult to distinguish. The atypical chemotype generally appears to have ± finer, but relatively compact podetia, almost exclusively dichotomously ramified, with a rather "bumpy" surface, covered with broad, relatively flat, closely adjoining packets of algae, giving the podetia a overall rather roughened surface aspect (see inset of Fig. 3d). In contrast, typical Cladonia confusa f. confusa (Fig. 3c) is characterized by mostly trichotomous ramifications, although specimens frequently also have dichotomously ramified podetia. In fact the majority of the terminal branches are dichotomous, only further down ramifications become increasinly trichotomous. Overall these typical specimens also have a more slender, less stout, less densely ramified appearance, though individual podecia are generally slightly thicker, i.e., generally somewhat broader in diameter. The different surface seems to be perphaps the most diagnostic morphological character of the two chemotypes: typical C. confusa f. confusa has packets of granular algae dispersed on an arachnoid stereome. Its surface appears overall rather smooth, though somewhat cottony and less compact, and as if peppered with granular packets of algae wrapped in hyphae. The other chemotype has a much more uneven surface and seems to lack the granular packets of algae; instead the packets of algae seem to be more closely incorporated into the stereome surface, causing the "bumpy" appearance. Nevertheless, how consistently these characters indeed correlate with the two chemotypes is quite diffcult to assess. To some extent the differences appear quite transient and we therefore hesitate to describe a new species here based on these rather inconspicous characters. Selected specimens examined : ECUADOR. GALAPAGOS: Fernandina Island, W-side, 335 m, transition zone, 15 Feb 1964, Cavagnaro (COLO 193423); green strip on SW slope, 4 Feb 1964, Cavagnaro 26 (duplicate ex US to H, dupl. to CDS). Isabela Island, Volcán Alcedo , outer SE-exposed slope, ca. 2.5 km below the crater rim, 0°26'20"S, 91°4'35"W, 784 m, transition zone, on rock, 7 Mar 2006, Bungartz, F. 4293 (CDS 28365), rim of caldera of Volcán Alcedo, S-side of crater on way to the fumaroles, 700 m, humid zone, on ground, 11 May 1976, Weber, W.A. (COLO 297127); Volcán Cerro Azul , S slope above Iguana Cove, 750 m, humid zone, 22 June 1976, Sipman, H.J.M. L-36 (COLO 297925, H, M, U, US), 700 m, humid zone, on rock, 22 June 1976, Sipman, H.J.M. L-43 (COLO 297918); Volcán Darwin , Cerro Beagle, dry zone, 15 June 1984, Luong, T.T. (CDS 10884), mountain E of Tagus Cove, 910 m, humid zone, Snodgrass, R.E . (CAS-DS 682613), southwestern slope, above Tagus Cove, 0°13'43.29"S, 91°19'47.3"W, 724 m, transition zone, on soil, 12 Nov 2007, Ertz, D. 11822 (CDS 37181); Volcán Sierra Negra , South side of Sierra Negra, trail to Alemania, 0°50'57.5"S, 91°7'41.3"W, 1020 m, humid zone, on soil, 16 Aug 2008, Herrera - Campos, M.A. 10694 (CDS 40432, 10702, 40440), close to the southern crater rim, along the trail to Alemania, 0°51'12.69"S, 91°8'40.5"W, 1055 m, humid zone, on soil and plant debris, 16 Aug 2008, Bungartz, F. 8345 (CDS 40991). Pinta Island , on top of the highest point of the island, 0°35'3"N, 90°45'12"W, 625 m, humid zone, on soil, 26 Feb 2007, Bungartz, F. 5742 (CDS 33393), E-slope of the highest crater, on highest rim of highest crater, 650 m, humid zone, on rock, 10 July 1976, Sipman, H.J.M. L-140 (COLO 297820, H, U). Pinzón Island , from the NE-coast to the highest summit, 350 m, transition zone, on rock, 2 July 1976, Sipman, H.J.M. L-95 (COLO 297865). San Cristóbal Island , Cerro San Joaquín, 0°53'49.5"S, 89°30'47.7"W, 691 m, humid zone, 24 Aug 2008, Herrera-Campos, M.A. 450 (CDS 43341), Volcán Santo Tomás, borde del cráter 0°50'0"S, 91°2'0"W, 1 Feb 1994, Follmann, G. 35302 (B-KOELN 60 0173576), bordering lake at El Junco, humid zone, on rock, 21 May 1976, Lanier, J. (COLO 298430), Wreck Bay, Stewart, A. 431 (339) (CAS-DS 640456, FH 197384), Anonymous collector 4759 (FH 197386), NE-slope of Cerro San Joaquín, shortly below the summit, 0°53'50.79"S, 89°30'49.7"W, 693 m, humid zone, on bryophytes, 24 Aug 2008, Bungartz, F. 8586 (CDS 41232). Santa Cruz Island , below El Puntudo, 720 m, humid zone, on soil, 18 Apr 1976, Weber, W.A. (CDS 10835), near Puntudo, 0°38'41"S, 90°20'13"W, 750 m, humid zone, on soil, 27 May 2005, Aptroot, A. 63203 (CDS 29934), along the trail from Media Luna to El Puntudo, at a small stream crossing the trail, 0°39'4"S, 90°20'5"W, 690 m, humid zone, on soil, 28 Feb 2006, Ziemmeck, F. 734 (CDS 27863), at the base of the eastern slope below the summit of El Puntudo, 0°38'42"S, 90°20'14"W, 780 m, humid zone, on soil, 28-Feb-2006, Bungartz, F. 3985 (CDS 27915), due N of Academy Bay, 610 m, humid zone, 20 Feb 1964, De Roy, A. (distributed by Weber as Lich. Exs. no. 105 to COLO 185829, H, M, NY, US, CAS-DS nos. 629519, 681394). : Published as part of Yánez-Ayabaca, A., Ahti, T. & Bungartz, F., 2013, The Family Cladoniaceae (Lecanorales) in the Galapagos Islands, pp. 1-33 in Phytotaxa 129 (1) on pages 12-13, DOI: 10.11646/phytotaxa.129.1.1, http://zenodo.org/record/5085561